Letter : Aid for Spain - Schevenels, Walther, b. 1894
032-0108-001 INTERNATIONAL FEDERATION OF TRADE UNIONS 9, Avenue d'Orsay, Paris-VIIe Sch/T Your Reference: HVT/EAB/DT/587. TELEGRAMS: INTERFED—PARIS TELEPHONE: INVALIDES 45-88 AFFILIATED COUNTRIES: ARGENTINE AUSTRIA BELGIUM CANADA CZECHOSLOVAKIA DANTZIG DENMARK DUTCH EAST INDIES ESTONIA FINLAND FRANCE GREAT BRITAIN GREECE HOLLAND HUNGARY INDIA LUXEMBURG MEMEL TERRITORY PALESTINE POLAND ROUMANIA SOUTH AFRICA SOUTH-WEST AFRICA SPAIN SWEDEN SWITZERLAND YUGOSLAVIA EXECUTIVE COMMITTEE: President W. M. Citrine, Great Britain; Vice-Presidents: H. Jacobsen, Denmark; L. Jouhaux, France; E. Kupers, Holland; Corn. Mertens, Belgium; R. Tayerle, Czechoslovakia; General Secretary: W. Schevenels. Letter: F. I. de Sol. No. 214 9th February, 1939. Mr. H.V. Tewson, Transport House, Smith Square, London, S.W.1. Dear Comrade Tewson, Aid for Spain. In reply to your letter of the 7th February regarding photographs of the work done by the International Solidarity Fund, to be included in your pamphlet, we will forward the matrices of our photographs either tomorrow or the day after tomorrow. With best wishes, Yours sincerely, W. Schevenels. General Secretary. 292/946/32/108